2001
DOI: 10.1111/j.1744-6570.2001.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Cognitive Ability as Predictors of Job Search Among Employed Managers

Abstract: Research on employee job search and separation traditionally focuses on situationally specific variables. Such variables may change with particular employment situations (e.g., job tenure, salary, perceived organizational success), they may be differentially relevant to work situations over time (e.g., education), or may reflect individual reactions to particular work situations (e.g., job satisfaction). More enduring individual characteristics, particularly personality and cognitive ability, may affect job se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
125
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(142 citation statements)
references
References 76 publications
10
125
0
7
Order By: Relevance
“…12 Our results mirror those of recent studies that show that both cognitive ability and character skills help to predict outcomes and behavior such as wages, workplace performance, educational attainment, marital status and the extent of job searching (Boudreau et al, 2001;Higgins et al, 2007;Heckman et al, 2006;Mueller and Plug, 2006;Duckworth et al, 2007;Cunha et al, 2010 Lindqvist andVestman, 2011;Burks et al, 2014;. To the extent that these outcomes and behaviors reflect a combination of analytic reasoning and the ability to understand well the intentions and beliefs of others, our results suggest one mechanism by which cognition and character may jointly be driving them.…”
supporting
confidence: 67%
“…12 Our results mirror those of recent studies that show that both cognitive ability and character skills help to predict outcomes and behavior such as wages, workplace performance, educational attainment, marital status and the extent of job searching (Boudreau et al, 2001;Higgins et al, 2007;Heckman et al, 2006;Mueller and Plug, 2006;Duckworth et al, 2007;Cunha et al, 2010 Lindqvist andVestman, 2011;Burks et al, 2014;. To the extent that these outcomes and behaviors reflect a combination of analytic reasoning and the ability to understand well the intentions and beliefs of others, our results suggest one mechanism by which cognition and character may jointly be driving them.…”
supporting
confidence: 67%
“…In a study by Khakpour et al in Iran, it has been found that, among personality traits, neuroticism-defined as the tendency to express anxiety, fear, negative affect or self-reproach -was significantly related to job performance (task-contextual) (26). In another study carried out by Boudreau et al neuroticism was shown to be related positively to job search (27). Michel et al, in a meta-analytic review have shown that it is related to negative work-nonwork spillover (β = -0.29) (28).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Khakpour et al, it has shown that, among personality traits, extroversion was also significantly related to job performance (task-contextual) (26). In the study of Boudreau et al, the relationship between extroversion and job search was significant and positive in the presence of situational factors, particularly job satisfaction (27). Michel et al in his metaanalytic review have shown extroversion is related to negative work-nonwork spillover (β = -0.08), and is related to positive worknonwork spillover (β = 0.27) (28).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between personality characteristics and career adaptability processes, and more specifically career planning, highlighting job-search or employability improvement processes, various authors have suggested that, depending on their personality characteristics, people can be predisposed to certain search processes (Boswell, Roehling & Boudreau, 2006;Boudreau, Boswell & Bretz, 2001;Brown, Cober, Kane, Levy & Shalhoop, 2006;Caldwell & Burger, 1998;Costa & McCrae, 1985Goldberg, 1990;Kanfer, Wanberg & Kantrowitz, 2001;Tziner, Vered & Ophir, 2004). In this sense, Boundreau et al (2001) state that a predisposition toward positively valuing life experiences and learning more from opportunities can aid in the interpretation of job situations and contribute to the job search and improved employability.…”
Section: Introductionmentioning
confidence: 99%